The identity construction of Iranian English students learning translated L1 and L2 short stories: Aspiration for language investment or consumption? - Shahidzade, Farangis; Mazdayasna, Golnar (Frontiers in Psychology, 2022)
A large number of investigations have highlighted the importance of incorporating literary texts into English language teaching programs. Nevertheless, there are scarce studies on how short stories from L1 and L2 literature play a role in reconstructing learner identity in tertiary contexts. The present research study examines the identities of four non-native undergraduate students concerning aspirations for language investment or consumption. Data collection instruments were semi-structured interviews, open-ended questionnaires, and diary writings. The materials taught in the course consisted of three translated Persian and four target fictions related to loyalty and justice. The researchers used qualitative content analysis to explore the language learners' self-images of initial, story-based, and prospective learning stages. Nearly all the participants regarded language learning as language consumption for pleasure in different stages except for the future aspiration stage; they did not aspire for personal economic benefits. The findings may enlighten curriculum designers in EFL contexts to incorporate literary texts from the native and target cultures into language education materials to provide opportunities for learners to experience diverse identities and meet individual preferences. Keywords: identity reconstruction, imagined community, language consumption, language investment, learner identity